Farmers' Access to Farm Programs of Bangladesh Betar: An Evaluation of Effectiveness - Hasan, Mahedi; Mondal, Nazrul Islam; Islam, Nurul; Hoque, Aminul (Indian Journal of Extension Education, 2017)
Different forms of farm programs (FP) have been being developed and aired by Bangladesh Betar (BB) for decades to  hasten the development of agriculture and the farming communities of Bangladesh. These programs are in dire need of  academic study for in-depth evaluation to discern their effectiveness. This study was supposed to reveal the effectiveness  of the FP of BB in respect of the extent to which it reaches the farmers of Bangladesh. Data and necessary information  were collected by means of document analysis and survey methods. A sample of 465 respondents was selected for  questionnaire survey. Frequency distribution and z-test for significance test of proportions were done for data analysis. It  was divulged that the FPs of BB were ineffectual because they failed to reach 93.33 per cent of the farmers. Radio set, a  culturally unfit device was possessed by only 4.30 per cent of the farmers. Most of the farmers were accustomed to  unauthorized sources (salesman and fellow farmers) of farm information. Avast majority of the respondents were insolent  towards the authorized extension agents and departments. The unconsciousness regarding the importance of farm  knowledge and their mindset were the most influencing factors for listening to the FPs. Initiatives were must to change the  long cherished mindset of the farmers and culturally fit devices were to be patronized in receiving the radio FPs.
Keywords: Bangladesh betar; farm programs; effectiveness of farm programs; farmers of bangladesh